Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. The reality of using distributed leadership in distance education in public schools in Al-KharjMrs. Asmaa Ahmed Al-Qahtani, Co-Prof. Abdulaziz Mohammed Al-Saqer2. Activating Educational Vouchers in Private Education Schools in the Light of the American Experience, Entrance to the Privatization of Public Education (proposed Concept)Mrs. Amal Muhammad Ali Al-Khudair , Dr. Nisreen Nasser Al-Sayari3. English distance learning difficulties in light of Corona pandemic from the perspective of primary school students in Alquwayiyah provinceMrs. Sara Saad Alyabis, Prof. Eman M. A. Alruaithi4. The objective of this Study is to identify the Effect of A program Based on the Mc Carthy Model (4 MAT) for the Development of Mental Motivation among the Student of 2nd Level, secondary School.Instructor \ Ahmed Saleh Abdulla Al- Kokabani, Co-Prof. Twfik Ali Alem5. The Common Bullying types on Students with Autism spectrum disorder and its reasons  from their Teachers’ Perspectives in the city of JeddahMrs. Walaa Awadh Almalki, Dr. Lama Abdul-Hakeem Sahab6. Quality of life and psychological compatibility in light of the precautionary measures of the Corona pandemic from the point of view of a sample of individuals in the city of Makkah Al-MukarramahMrs. Badryah Faisal Alghamdi, Mrs. Sawsan Mohammed Neyaz, Mrs. Wafa Ahmed Alomari7. The effectiveness of a counseling program based on positive thinking skills to reduce  the alienation on a sample of anonymous descendant in the orphanage in RiyadhMrs. Sara Ayed Al-Zahrani, Prof. Ali Saeed Al-Amri
Keywords: Journal of Educational and Psychological Sciences